2014
DOI: 10.3109/09638237.2014.971143
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy for older adults with depression: a review

Abstract: Given that many older adults with depression are reluctant to accept antidepressant medication or unable to tolerate their side effects, CBT can be used as an option in treating depression in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…Therefore, when treating depression among older adults, it is recommended that medication with antidepressants be accompanied by a course of psychosocial therapy as well (Blackburn, Wilkins, & Wiese, 2017;Lill, 2015). The effectiveness of methods such as problem-solving therapy, interpersonal therapy, cognitive behavioural therapy, spiritual reminiscence therapy and mindful yoga has been reported (Jayasekara et al, 2015;Jonsson et al, 2016;Lee, Tang, & Bressington, 2019;Syed Elias et al, 2019). It has also been reported that experienced nurses sometimes monitor depressive symptoms by engaging their patients in conversation to properly address depression among older adults (Waterworth, Arroll, Raphael, Parsons, & Gott, 2015).…”
mentioning
confidence: 99%
“…Therefore, when treating depression among older adults, it is recommended that medication with antidepressants be accompanied by a course of psychosocial therapy as well (Blackburn, Wilkins, & Wiese, 2017;Lill, 2015). The effectiveness of methods such as problem-solving therapy, interpersonal therapy, cognitive behavioural therapy, spiritual reminiscence therapy and mindful yoga has been reported (Jayasekara et al, 2015;Jonsson et al, 2016;Lee, Tang, & Bressington, 2019;Syed Elias et al, 2019). It has also been reported that experienced nurses sometimes monitor depressive symptoms by engaging their patients in conversation to properly address depression among older adults (Waterworth, Arroll, Raphael, Parsons, & Gott, 2015).…”
mentioning
confidence: 99%
“…Such intervention studies could demonstrate the causal role of hedonic well‐being in promoting more advantageous disability trajectories over time. Some such interventions have been previously developed (Friedman et al., ; Ho, Yeung, & Kwok, ) and may prove to be beneficial clinical and preventative tools for preventing disability progression (Friedman et al., ; Jayasekara et al., ). Since both the medium increasing disability class and the high stable disability class show lower mean levels of hedonic well‐being compared to the normative class, interventions increasing hedonic well‐being can benefit both these vulnerable classes and ultimately lead to better health in the aging population.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of these factors will help identify subgroups at greatest risk for increases in functional limitations (or disability) as well as those at reduced risk due to protective factors such as psychological well‐being , thereby broadly informing future efforts aimed at preserving the quality of life in aging adults. From our evaluation, if we find that both eudaimonic and hedonic well‐being are protective for disability progression, then cognitive behavior therapies targeting eudaimonic well‐being (Friedman et al., ) and hedonic well‐being (Friedman et al., ; Jayasekara et al., ) that have shown effectiveness in improving psychological well‐being could be implemented to forestall functional declines over time.…”
Section: Introductionmentioning
confidence: 91%
“…A moderator may be a variable that is not manipulated such as gender or age. For example it is possible that CBT for depression is more or less effective for different age groups (Jayasekara et al, 2015) as age may change the efficacy of CBT. Moderators may also be experimentally manipulated.…”
Section: Moderationmentioning
confidence: 99%